Saat Tarekat Melawan Kapitalisme Global: Murabitun World Movement di Indonesia, 1999-2020 - Haryo Mojopahit (Socio Historica: Journal of Islamic Social History, 2022)
This study will discuss the history of Murabitun World Movement (MWM) in Indonesia and its activities, especially its economy of giving ideas, activities, and networks. MWM is a religious movement that was founded by Ian Dallas, or Abdul Qadir As-Sufi. The movement is fuelled by a sufi order called al-Shadhili al- Darqawiyya Habibi and based on the Maliki school. Mostly, sufi orders are based on asceticism. However, MWM have their own perspectives on Occidentalism, politics, and economy, particularly economy of giving. The movement views the Western civilization as a peril in human history. It also concludes that the Western’s capitalism order and paper moneys as a source of injustice in global economy and poverty in Muslim world. MWM’s mission is to bring back justice and fairness in global economy and politics by encouraging gold and silver coins (dinar and dirham) as real exchange currencies. In Indonesia, MWM’s ideas and activities have been promoted since 1998. A few years later it succeeds in bringing the ideas of using dinar and dirham to the Indonesian Muslim Scholars Society or ICMI annual conference. The leadership of MWM also could bring the President of ICMI, Adi Sasono, to visit Abdul Qadir As-Sufi in Morocco. MWM believes that a welfare state is a utopia if a country still follows capitalism and usury (riba). A state only can provide welfare to its citizens if they implement sixteen pillars of welfare in Islam. Most of these requirements are concepts in Islamic philanthropy. However, MWM has unique interpretations and practices regarding the Islamic philanthropy. The MWM in Indonesia became famous after the Indonesian government accused Zaim Saidi, the Emir of MWM in Indonesia, of violating the Currency Bill. However, he was released by the Court.     Studi ini mendiskusikan sejarah Murabitun World Movement (MWM) di Indonesia dan aktivitasnya, terutama yang terkait dengan gagasan ekonomi kedermawanan, aktivitas-aktivitasnya, beserta jaringannya. MWM atau Gerakan Murabitun Se-Dunia adalah sebuah gerakan keagamaan yang didirikan oleh Ian Dallas atau Abdul Qadir As-Sufi. Gerakan ini dijiwai oleh tarekat tasawuf Syaidziliah Darqawiyah Habibi dan berdasarkan mazhab Maliki. Kebanyakan gerakan tarekat didasarkan oleh asketisme atau menjauhi kehidupan dunia. Namun, MWM memiliki pandangan tersendiri mengenai oksidentalisme, politik, ekonomi, dan filantropi Islam. Gerakan ini melihat bahwa peradaban Barat merupakan penyebab kehancuran dalam sejarah manusia. MWM juga menyimpulkan bahwa tatanan kapitalisme global Barat dan uang kertas sebagai penyebab dari ketidakadilan ekonomi dan kemiskinan di dunia Islam. Misi dari MWM adalah membangun kembali tatanan ekonomi dan politik dunia yang adil melalui gerakan kembali kepada koin emas dan perak (dinar dan dirham) sebagai alat tukar. Di Indonesia, pemikiran dan kegiatan MWM telah tumbuh sejak tahun 1998. Beberapa tahun setelahnya, MWM berhasil memasukan penggunaan dinar dan dirham dalam Musyawarah Nasional Ikatan Cendekiawan Muslim Indonesia (ICMI). Para pelopor MWM di Indonesia bahkan dapat mengajak Ketua ICMI saat itu, Adi Sasono, untuk bertemu dengan Abdul Qadir As-Sufi di Maroko. MWM berkeyakinan bahwa negara kesejahteraan hanyalah impian jika masih mengikuti sistem kapitalisme dan riba. Sebuah negara hanya akan bisa memberikan kesejahteraan bagi rakyatnya jika dan hanya jika menerapkan enam belas pilar kesejahteraan dalam Islam yang sebagian besar pilarnya adalah konsep-konsep filantropi Islam. Namun, konsep-konsep filantropi Islam yang ditawarkan MWM dapat dikatakan cukup unik dibandingkan pemahaman mayoritas. MWM ramai dibahas di publik ketika Zaim Saidi, Amir MWM Indonesia, ditangkap oleh aparat yang berwenang karena dianggap melanggar Undang-Undang No. 1 tahun 1946 tentang Mata Uang. Namun, tuduhan tersebut tidak terbukti dan Zaim Saidi dibebaskan dari dakwaan oleh Pengadilan Negeri Depok.